PERANAN BERITA ACARA PEMERIKSAAN LABORATORIS KRIMINALISTIK DALAM PEMBUKTIAN DI PERSIDANGAN (STUDI PUTUSAN NOMOR 118/PID.SUS/2019/PN SKT) - Bramasto, Alwin Bobby; Harjono, Harjono (Sebelas Maret University, 2023)
This article analyzes the role of documentary evidence in the form of minutes of laboratory examination in the evidence at trial in the Decision. Number 118/Pid.Sus/2019/Pn Skt. This research uses a normative research type and is perspective and applied. This legal research uses a case approach. The basis for this approach is the ratio decidendi or reasoning, namely the judge's reasons for arriving at a decision. The source of research materials uses two materials, namely primary legal materials and secondary legal materials. The data collection technique used was document study (literary study) and the data analysis technique used was the syllogistic method using a deductive mindset. In the results of the discussion and research results here, the documentary evidence in the form of minutes of laboratory examinations has an important role in proving in the cases being studied, namely being considered by the Judge in proving the charges filed by the Public Prosecutor. The judge in this case has decided the case in accordance with the provisions of the Criminal Procedure Code because he has considered at least two valid pieces of evidence and has also considered the facts at trial.